PENGEMBANGAN MEDIA SMOBI (SMART BOX PERUBAHAN ENERGI) MATA PELAJARAN IPA KELAS IV SD - Ratna Nur Hamidah; Bagus Amirul Mukmin; Elis Irmayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by a problem identified by the researcher, namely that teachers rarely use instructional media and tend to rely on lecture and question-and-answer methods. Based on a student needs questionnaire, 83% of students reported difficulty in understanding the topic of energy transformation in science lessons. This is evidenced by the fact that 9 out of 15 fourth-grade students at SDN Mojokambang 2 scored below 75. Additionally, 60% of students stated that learning activities did not include any games. In response to these issues, this study aims to develop SMOBI (Smart Box for Energy Transformation), an instructional media that is valid, practical, and effective as a teaching aid for fourth-grade science lessons on energy transformation. This research uses the R&D method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The validity of the SMOBI media was assessed with a score of 85% from material experts and 83.3% from media experts, categorizing it as highly valid. Its practicality was evaluated through questionnaires: the teacher respondents gave a score of 87.5%, while student respondents in small-group testing gave a score of 94%, and in large-group testing, a score of 95%, classifying it as highly practical. The effectiveness of SMOBI was based on students' mastery in answering evaluation questions, with 12 out of 15 students achieving mastery, resulting in an effectiveness rate of 86.6%, which is considered highly effective. SMOBI can be used in the learning process to improve student learning outcomes, increase student engagement, and assist in understanding the material.